2021
DOI: 10.1097/meg.0000000000002100
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori eradication following first-line treatment failure in Europe: What, how and when chose among different standard regimens? A systematic review

Abstract: Cure rate following standard first-line regimens for Helicobacter pylori eradication is decreasing so several patients require two or more treatments. Antibiotic susceptibility-based therapy, advised in current guidelines, is largely impracticable in clinical practice. Some 'standard' regimens (triple therapies based on either levofloxacin or rifabutin, bismuth-based quadruple therapies, sequential, concomitant and hybrid therapies) were empirically used as rescue therapies. We performed a systematic review on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, a tailored sequence has been reported for these patients [53]. Of note, data from a systematic review, including recent studies on rescue therapy for H. pylori infection performed in European countries, found similar results [54]. Therefore, the therapeutic sequence we proposed could also be applied in other geographic areas.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…On the other hand, a tailored sequence has been reported for these patients [53]. Of note, data from a systematic review, including recent studies on rescue therapy for H. pylori infection performed in European countries, found similar results [54]. Therefore, the therapeutic sequence we proposed could also be applied in other geographic areas.…”
Section: Discussionmentioning
confidence: 75%
“…Unexpectedly, no data were available on concomitant, hybrid and high-dose dual therapy. Interest in the last regimen was recently renewed, even as a first-line therapy [ 54 ]. Data of 3 meta-analyses found that dual therapy with high-dose PPI and amoxicillin achieved similar eradication rates to levofloxacin-based, rifabutin-based and bismuth-based quadruple therapies when used as rescue therapy, but with a significantly lower side-effect rate [ 55 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, data from a recent systematic review showed that by adopting an empiric therapeutic sequence with bismuth-based quadruple therapy, levofloxacin- and rifabutin-based regimens following first-line therapy failure, H. pylori infection might be cured in virtually all patients, with only 1 in every 170 patients eventually remaining infected [ 67 ]. Therefore, the real advantage of resorting to bacterial susceptibility testing before third-line therapy, as suggested in the current guidelines [ 7 , 8 ], probably needs to be corroborated by further data.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were selected based on PICOS (population, intervention, comparators, outcomes, and study design) eligibility criteria. The inclusion standards were as follows: (a) subjects with Hp-positive and without region, sex, and age restrictions; (b) both control group (defined as patients treated with only Western medicine) and experimental group (defined as patients treated with TCM combined with Western medicine) have received the first-line therapy regimens [ 8 ] recommended in the current Consensus Report and failed to eradicate Hp; (c) TCM treatments in the experimental group include single herb, formulas, or herbal products in any formulations such as oral decoction, pill, powder, or granules; (d) randomized controlled and parallel trials were performed, regardless of whether blinding was adopted, and had a duration of at least one week; and (e) the trial included outcome indicators with Hp eradication rates at least. The definition of the Hp eradication rates must conform to the requirements of the current Consensus Report.…”
Section: Methodsmentioning
confidence: 99%
“…However, the eradication rate decreased year by year due to bacterial factors, patient compliance, and reinfection; among which, antibiotic resistance is the most important factor [ 7 ] and resistance to clarithromycin is particularly serious. For patients who were treated with triple therapy yet failed, a bismuth quadruple therapy (such as metronidazole, tetracycline, bismuth, and a PPI) is recommended [ 8 ]. Nevertheless, the resistance rate of metronidazole and tetracycline has also exceeded 15% globally [ 9 ].…”
Section: Introductionmentioning
confidence: 99%